2017
DOI: 10.1016/j.jshs.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation and return to sport after hamstring strain injury

Abstract: Hamstring strain injuries are common among sports that involve sprinting, kicking, and high-speed skilled movements or extensive muscle lengthening-type maneuvers with hip flexion and knee extension. These injuries present the challenge of significant recovery time and a lengthy period of increased susceptibility for recurrent injury. Nearly one third of hamstring strains recur within the first year following return to sport with subsequent injuries often being more severe than the original. This high re-injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 97 publications
(259 reference statements)
0
88
0
6
Order By: Relevance
“…17 Given the high re-injury rate, 18 many authors have suggested using a sport-specific approach in the rehabilitation phase to ensure an optimal return-toplay scenario, permitting the player to perform at pre-injury levels without pain and maintain performance, and at the same time reduce the risk of reinjury. 19 Although many return-to-play programs have been reported in the literature, 20 to the best of our knowledge there are no soccerspecific programs dealing with rehabilitation following an injury to a muscle of the hamstring muscle group that integrates PNE and Rehab & Reconditioning Program (RRP).…”
Section: Introductionmentioning
confidence: 99%
“…17 Given the high re-injury rate, 18 many authors have suggested using a sport-specific approach in the rehabilitation phase to ensure an optimal return-toplay scenario, permitting the player to perform at pre-injury levels without pain and maintain performance, and at the same time reduce the risk of reinjury. 19 Although many return-to-play programs have been reported in the literature, 20 to the best of our knowledge there are no soccerspecific programs dealing with rehabilitation following an injury to a muscle of the hamstring muscle group that integrates PNE and Rehab & Reconditioning Program (RRP).…”
Section: Introductionmentioning
confidence: 99%
“…Lower limb movement analysis has been addressed in several studies to determine the sequence of contraction of posterior and anterior muscles of the thigh [1] muscle force characterization is increasingly important in rehabilitation and sports m [2], especially for elite athletes [3, injuries occur during sports when the athlete, during terminal swing phase of running [5] extends the lower limb beyond limits. Rehabilitation is very important after injuries or surgical repair.…”
Section: Introductionmentioning
confidence: 99%
“…24 Another possible cause cited in the literature is incomplete rehabilitation by forcing an early return to play. 25 This implies that although the previously mentioned protocols, programs, and exercises have shown to be effective with the general athletic population, there appears to be a need for a soccer-specific rehabilitation program.…”
mentioning
confidence: 99%